Image Analysis and Evaluation of Cylinder Bore Surfaces in Micrographs - Wang, Limeng (Forschungsberichte aus der Industriellen Informationstechnik / Institut für Industrielle Informationstechnik (IIIT), Karlsruher Institut für Technologie, 2013)
This work presents two image-based inspection approaches for the quality evaluation of cylinder bore surfaces. In the first algorithm, metal folds on plateau-honed surfaces are inspected with scanning electron microscopy. An edge-aware structure tensor is proposed for feature extraction and localization of surface defects. The second algorithm uses a morphgraphical method for detecting graphite grains in optical micrographs. Based on the inspection results, quality parameters are proposed.